Racial Discrimination in The First Grader Movie - Ro'is, Syamsuddin; Harida, Ratri (SALIENCE: English Language, Literature, and Education Journal, 2024)
Racial discrimination is one of the social phenomena that causes intergenerational trauma. The movie becomes one way to picture this reality, as in The First Grader. Using content analysis to qualitatively describe the phenomena, the researcher found three levels of racism. The findings show that personalized mediate racism happens the most. The next level of racism that occurs is institutionalized racism and internalized racism. The source of the racism is British colonialism in Kenya and tribalism, which have had lasting effects on the social fabric of the country. The movie effectively portrays how these different levels of racism manifest in everyday life. The First Grader serves as a powerful reminder of the ongoing struggle against racial discrimination and the importance of addressing its root causes to prevent further intergenerational trauma.